Simplifying
5C + -4 + -2C + 1 = 8C + 2
Reorder the terms:
-4 + 1 + 5C + -2C = 8C + 2
Combine like terms: -4 + 1 = -3
-3 + 5C + -2C = 8C + 2
Combine like terms: 5C + -2C = 3C
-3 + 3C = 8C + 2
Reorder the terms:
-3 + 3C = 2 + 8C
Solving
-3 + 3C = 2 + 8C
Solving for variable 'C'.
Move all terms containing C to the left, all other terms to the right.
Add '-8C' to each side of the equation.
-3 + 3C + -8C = 2 + 8C + -8C Combine like terms: 3C + -8C = -5C<span>-3 + -5C = 2 + 8C + -8C
Combine like terms: 8C + -8C = 0
-3 + -5C = 2 + 0
-3 + -5C = 2
Add '3' to each side of the equation.
-3 + 3 + -5C = 2 + 3
Combine like terms: -3 + 3 = 0
0 + -5C = 2 + 3
-5C = 2 + 3
Combine like terms: 2 + 3 = 5
-5C = 5
Divide each side by '-5'.
C = -1
Simplifying
C = -1</span>
Answer: 2
Step-by-step explanation:
Answer:
When x=8, y=-6. When x=10, y=0
Step-by-step explanation:
![y=3x-30\\x^2+y^2=100](https://tex.z-dn.net/?f=y%3D3x-30%5C%5Cx%5E2%2By%5E2%3D100)
You can plug the given y value into the second equation to get:
![x^2+(3x-30)^2=100\\x^2+9x^2-180x+900=100\\10x^2-180x+800=0\\10(x^2-18x+80)=0\\10(x-8)(x+10)=0\\x= 8, 10\\y= -6, 0](https://tex.z-dn.net/?f=x%5E2%2B%283x-30%29%5E2%3D100%5C%5Cx%5E2%2B9x%5E2-180x%2B900%3D100%5C%5C10x%5E2-180x%2B800%3D0%5C%5C10%28x%5E2-18x%2B80%29%3D0%5C%5C10%28x-8%29%28x%2B10%29%3D0%5C%5Cx%3D%208%2C%2010%5C%5Cy%3D%20-6%2C%200)
Hope this helps!
Answer:
5
Step-by-step explanation:
I subtracted